POU-M2 promotes juvenile hormone biosynthesis by directly activating the transcription of juvenile hormone synthetic enzyme genes in Bombyx mori. Issue 4 (6th April 2022) - Cai, Rui; Tao, Gang; Zhao, Ping; Xia, Qingyou; He, Huawei; Wang, Yejing
Abstract : Abstract : Juvenile hormone (JH) plays a key role in preventing larval precocious metamorphosis, maintaining larval state, controlling adult sexual development and promoting insect egg maturation. Genetic studies have shown that POU factor ventral veins lacking regulates JH synthesis to control the timing of insect metamorphosis. However, how POU factor regulates JH synthesis is largely unknown. Here, we found POU-M2 was highly expressed in corpora allata (CA) and specifically localized in the nucleus of CA. The overexpression of POU-M2 promoted the expression of JH synthase genes and kr-h1 and enhanced the activity of JH synthase genes promoter. Further, POU-M2 promoted the transcription of JH acid O-methyltransferase (JHAMT) by directly binding to the key cis-regulatory elements -207, -249 and -453 within the proximal regions of JHAMT promoter. Both the POU domain and homeodomain were vital for the activation of POU-M2 on JHAMT transcription. Our study reveals the mechanism by which POU-M2 regulates JHAMT transcription.